HIGH SCHOOL BIOLOGY TOPICS THAT PERCEIVED DIFFICULT BY UNDERGRADUATE STUDENTS - Fauzi, Ahmad; Mitalistiani, Mitalistiani (Universitas Muhammadiyah Palembang, 2018)
Biology is a science subject which on the one hand becomes a favorite subject for many students, but on the other hand has many topics that are considered difficult by many students. The aims of this study was to map the difficult topics of biology in senior high school based on the opinion of undergraduate students. This present study used survey research design. The participant of this study was the undergraduate student of class of 2017 majoring in Biology in one of the state universities in Malang. The instrument used in this study was a questionnaire of difficulty topics on high school biology subject and descriptive analysis was used as data analysis techniques. The result of this study was Genetics, Metabolism, and Cell Division were the first, second, and third most difficult topics in XII grade. The Immune System, the Coordination System, and the Plant Tissue were the first, second, and third most difficult topic in XI grade. Protista, Monera, and Virus were the first, second, and third most difficult topics in X grade. Genetics, Immune System, and Metabolism also selected into three topics of all grades that were considered most difficult by undergraduate students majoring in Biology.Â Biologi merupakan mata pelajaran sains yang di satu sisi menjadi mata pelajaran favorit bagi banyak siswa, namun di sisi lain memiliki banyak topik yang dianggap sulit oleh banyak siswa. Tujuan dari studi ini adalah untuk memetakan topik-topik biologi di Sekolah Menengah Atas (SMA) yang dianggap sulit berdasarkan pendapat mahasiswa-mahasiswa S1. Studi ini menggunakan desain penelitian survai. Partisipan pada studi ini adalah mahasiswa S1 angkatan 2017 Jurusan Biologi di salah satu universitas negeri di Malang. Instrumen yang digunakan pada studi ini adalah angket topik-topik sulit pada mata pelajaran Biologi SMA dan analisis deskriptif digunakan sebagai teknik analisis data. Hasil penelitian ini adalah Genetika, Metabolisme, dan Pembelahan Sel merupakan topik tersulit pertama, kedua, dan ketiga di kelas XII. Sistem Imun, Sistem Koordinasi, dan Jaringan Tumbuhan merupakan topik tersulit pertama, kedua dan ketiga dikelas XI. Protista, Monera, dan Virus merupakan topik tersulit pertama, kedua, dan ketiga di kelas X. Genetika, Sistem Imun, dan Metabolisme juga terpilih sebagai tiga topik dari seluruh kelas yang dianggap tersulit bagi mahasiswa Jurusan Biologi.